New Exact Explicit Nonlinear Wave Solutions for the Broer-Kaup Equation - Zhenshu Wen (Journal of Applied Mathematics)
We study the nonlinear wave solutions for the Broer-Kaup equation. Many exact explicit expressions of the nonlinear wave solutions for the equation are obtained by exploiting the bifurcation method and qualitative theory of dynamical systems. These solutions contain solitary wave solutions, singular solutions, periodic singular solutions, and kink-shaped solutions, most of which are new. Some previous results are extended.